KAJIAN TEKNOLOGI PROSES DAN HARGA POKOK PRODUKSI MASSA COR “CN7” DENGAN SISTEM PEMBEBANAN BERBASIS AKTIVITAS, DAN IMPLIKASINYA TERHADAP HARGA TRANSFER DAN PERSEDIAAN - I Nyoman Normal; Wiryawan Suputra Gumi (Forum Manajemen STIMI Handayani Denpasar, 2013)
The aims of this research relate to casting massa“CN7” (40% SukaBumi Blend : 25% RRT Feldspar : 20% Caolin : 2,5% Ball Clay : 12,5% Cuarsa)were : (1) To determine process technology casting massa“CN7”; (2) To calculatecost of good manufactured; (3) To determine transfer price; and (4) To recognizedending inventory that reported on balance sheet. The research results shew that :(1) The process technology casting massa“CN7” according to production functionwere : weighting process,grussing process, mixing process, filtring process, andcarrying process; (2)Cost of good manufacturedcor massa“CN7” according toActivity Based Costing (ABC) systems was Rp 2.896,83 each unit, that followed byraw materal cost Rp 1.960,00, direct labour cost Rp 860,84, variable overhead costRp 39,89, and fixed overhead cost Rp 36,09; (3) The transfer price casting massa“CN7”according to full cost transfer pricing methodwas Rp 3.302,39each unit, thattransfer priceformed by cost of good manufactured Rp 2.896,83, operating expenseRp 289,68 (marketing expense Rp 173,81 and general & administration expense Rp115,87), and expected margin Rp 115,87; and (4) Ending inventory casting massa“CN2” according to specific identification method was Rp 434.524,50.